2022
DOI: 10.3389/fnut.2022.893963
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Regarding the Adherence to the Mediterranean Diet Among Older Adults Living in Lebanon and Syria

Abstract: The Mediterranean diet (MedDiet) has been associated with many health benefits. Poor adherence to MedDiet has been found among Lebanese adults, while in Syria, little is known about the adherence to MedDiet. A quantitative research approach was used, and data were collected through convenience sampling. The structure of the survey included the socio-economic and demographic data and the validated 14-point MedDiet assessment tool. The target population included 367 Lebanese and Syrian adults respectively residi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Another predictor of the athletic performance was the lean muscle mass, which has a strong positive correlation with the resting metabolism, HGS and iron intake, but is negatively correlated with energy intake. The muscle mass is determined by the protein status of an individual, and for activity of the muscle cell, iron is very important (American Dietetic Association et al, 2009;Karam et al, 2022b). Our findings were in agreement with a previous study showing a significant correlation between NK and NP scores of athletes (Hornstrom et al, 2011), but in disagreement with Torres-McG ehee et al (2012) research.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Another predictor of the athletic performance was the lean muscle mass, which has a strong positive correlation with the resting metabolism, HGS and iron intake, but is negatively correlated with energy intake. The muscle mass is determined by the protein status of an individual, and for activity of the muscle cell, iron is very important (American Dietetic Association et al, 2009;Karam et al, 2022b). Our findings were in agreement with a previous study showing a significant correlation between NK and NP scores of athletes (Hornstrom et al, 2011), but in disagreement with Torres-McG ehee et al (2012) research.…”
Section: Discussionsupporting
confidence: 80%
“…Another predictor of the athletic performance was the lean muscle mass, which has a strong positive correlation with the resting metabolism, HGS and iron intake, but is negatively correlated with energy intake. The muscle mass is determined by the protein status of an individual, and for activity of the muscle cell, iron is very important (American Dietetic Association et al , 2009; Karam et al , 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…For example from the Levant, a study done in Lebanon showed low adherence to MD with a mean score of (4.2) based on a scale of 10 items [30]. Similarly, another study showed the majority of Lebanese participants falling between low and moderate adherence and only 13% of study participants with high adherence (11).While in a more recent nding (2022), 47.42% of participants reported high adherence to MD (> 9), with a mean of (7.82 ± 2.32) [31]. Results from European Prospective Investigation into Cancer Italian cohort have shown that only 22% of participants only had high adherence participants [13].…”
Section: Discussionmentioning
confidence: 89%
“…The MD is popular with students, adults, and the elderly (72)(73)(74). The extensive research of the MD in the field of cancer demonstrates its enormous potential for both cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%